Pendampingan Digital Marketing, Branding dan Rebranding Sebagai Upaya Pengembangan Brand UMKM Desa Musir Lor - Hendra Maulana; Hakim Bima Ardimas Alam; Abd. Ghofar; Ilham Rahmatullah; Abyansyah Hayyu Sarwono; Zumrotul Liana Putri (Institut Nalanda, 2023)
Digital marketing can be a solution to solving problems that have been experienced by MSME actors, namely product marketing problems. Especially in Musir lor Village, Kec. Rejoso, Kab. Ngajuk, East Java Province, where there are several UMKM that have the potential to be developed to become more productive. However, the lack of understanding of digital marketing causes these UMKM to not develop further on a large scale. This is based on the results of observations and the implementation of location surveys in the village of Musir Lor which is a form of research method in the analysis of problems with Musir Lor UMKM owners, namely the lack of awareness of the residents of Musir Lor Village about the importance of Business Identification Numbers, as well as the lack of understanding in increasing business value. or the image of a product to support product quality improvement and increase the interest of potential consumers in an UMKM product. Some UMKM build businesses with minimal knowledge of UMKM business owners causing a lack of knowledge about product brands. Therefore, in branding or rebranding a product, it must be understood that an attractive, unique and easily recognized design is very important. Therefore, several alternative strategies that need to be considered in building a brand are logos that are appropriate to the line of business, banners and business stamps, more attractive and modern packaging designs. In this modern and technological era, it is certainly not far from operating digital applications that must be understood by UMKM business actors as a form of effort to increase the development of an UMKM, such as operating an online marketplace, social media and operating a financial management application to manage finances in a structured manner.